1028 Sleep and Enteric Disease: Sleep Now for Less Diarrhea Later. (27th May 2020) - Mantua, J; Gutierrez, R L; Isidean, S D; Alaca, A N; Testa, K J; Talaat, K; Doty, T J; Capaldi, V F; Porter, C
Abstract: Introduction: The bi-directional relationship between sleep and immune function is well-established. Sufficient sleep supports immune health and can increase vaccine efficacy. Conversely, sickness can disturb sleep quality, which can delay recovery and waking functioning. However, the bidirectional relationship between sleep and infectious diarrhea, the leading infectious disease threat to deployed military populations, has not been studied. We assessed the bi-directional relationship between sleep and enteric disease utilizing data from a recently-completed controlled human infection model (CHIM) with enterotoxigenic Escherichia coli (ETEC). Methods: During a CHIM to assess the efficacy of an immunoprophylactic targeting ETEC (NCT03040687), we measured sleep via actigraphy over an 8-day inpatient period. Participants ingested prophylaxis 3 times/day during days -2 and -1 and ingested ETEC on day 0. The primary outcome was moderate-severe diarrhea following the ETEC challenge. We hypothesized better sleep pre-challenge would reduce risk of disease after the challenge (assessed using linear regression). We also hypothesized total sleep time (TST) and sleep efficiency (SE) after the challenge would be lower/poorer than baseline (assessed using paired t-test). Results: Among 59 participants (aged 34.4±8.1yrs, 64% female), longer TST the night preceding ETEC challenge was associated with lower total diarrhea volume (B=-3.13, p=.001). SE was slightly but significantly poorer after the challenge (78 vs. 76%; t(55)=2.2, p=.03), but there was no significant change in TST, potentially due to low TST pre-challenge (316 vs. 329 minutes; p=0.12). Conclusion: These results - in aggregation with previous work on sleep and vaccines - suggest military sleep regulations should be put in place to increase sleep prior to traveling to an area of responsibility with high risk for enteric disease. These minor behavioral changes could provide lasting benefits to readiness of military servicemembers. Support: This work was supported by Joint Warfighter Medical Research Program (JWMRP) and the Military Operational Medicine Research Program (MOMRP). The opinions and assertions contained herein are the private views of the authors and are not to be construed as official or as reflecting the views of the US Army or of the US Department of Defense. This abstract has been approved for public release with unlimited distribution.